La ley orgánica de comunicación, observada desde el contenido de diario extra, antes y después de su promulgación - Aleaga Ramírez, Edisson Roberto (2016)
Press freedom has always been a recurring obstacle every incumbent government and the expressive profligacy has become a sort of media hegemony that became another stumbling block but not for the powerful but for the disadvantaged. Against all this-and approach the government of Rafael Correa, the Communications Law was created as a kind of legal mechanism to regulate and indirectly -of way, control the content that the media offer the audience…….